The Italian occupation of Fezzan and the role of national leaders in confronting the occupation 1913 –1914 (Journal of Human Sciences, 2021)
The current study aims to show a part of Libyan local history, specifically the first Italian occupation of Fezzan in 1913. It's most important pillars and circumstances and  the role of popular resistance in addressing it. This study also focuses on the most important tribal figures who fought colonialism, and follows the stages of the emergence of the idea of leadership, and leadership in the war following the signing of the O'Shea Lausanne Convention 1912. And some aspects of the leadership conflict that took place in that period between the resistance and non-resistance Supporters. As well as this paper contained in some detail  in the names of the most important tribes and  their leader in Fezzan and their great success in sparing the region leadership disputes over leadership such as that occurred in the western region Tripoli and Nafusa  Mountains, and their success in expelling Italian colonialism from Fezzan during the period 1914 – 1924.